Kualitas Pelayanan Publik di Kantor Kepala Desa Sukajadi Kecamatan Sadananya Kabupaten Ciamis - Muhamad Rifki Siddiq; Arie Budiawan; Ii Sujai (Papsel Journal of Humanities and Policy, 2024)
This research is motivated by the non-optimal public services at the Sukajadi Village head office, Sadananya District, Ciamis Regency. The method used in this research is qualitative research method. Data collection techniques in this study are literature study, field study (observation and interviews) and documentation. The informants in this study were 7 people. Data analysis techniques in this study use data reduction, data presentation, conclusions and verification. This study aims to determine how the quality of public services in the office of the village head of Sukajadi, Sadananya sub-district, Ciamis Regency. The author uses qualitative data analysis techniques through data processing of interview results and observation results to draw conclusions so as to answer the problems in the study. The results showed that public services in the office of the head of Sukajadi Village, Sadananya District, Ciamis Regency have been running but not optimal because problems are still found, namely: The discipline of officers who are still low in providing services to the community, the Village E-Office application has not been operated in services, there is still a lack of accuracy / caution of officers in processing services, and there are still delays in the service process being carried out.Keywords: Service Quality, Public Services, Administrative Services, Village, Village Government